Association of Lipoprotein-associated phospholipase A2 activity with components of the metabolic syndrome in apparently healthy boys - Hirschler, Valeria (2011)
Abstract: Background: Lipoprotein-associated phospholipase A2 (Lp-PLA2) has been proposed as a biomarker of risk of cardiovascular disease (CVD). Objective: To determine the association between Lp-PLA2 activity and BMI, insulin-resistance, components of the metabolic syndrome (MS), and lifestyle behaviors in healthy adolescent boys. Methods: Data were collected cross-sectionally from 164 adolescents from an amateur rugby club. BMI, blood pressure (BP), Tanner stages, glucose, insulin, lipids, and Lp-PLA2 activity were measured. Questionnaires for lifestyle behaviors were completed. Results: Approximately 26% of the adolescents were obese and 23% overweight. There was a univariate association between Lp-PLA2 and BMI (r=0.16;p=0.042), triglycerides (r=0.26;p=0.001), LDL-C (r=0.46;p<0.001), apo B (r=0.55;p<0.001), whereas waist circumference, BP, glucose, HOMA-IR, and HDL-C were not correlated. None of the lifestyle behaviors were significantly correlated with Lp-PLA2. In order to analyze Lp-PLA2 association with known CVD risk conditions, adolescents were categorized according to overweight/obesity and to the presence of metabolic syndrome. Conversely, as it was for LDL-C and apo B concentration, Lp-PLA2 activity was not higher in adolescents with obesity. Multiple regression analysis showed that apo B was significantly associated with Lp-PLA2 adjusted for age, BMI, triglyc-erides and LDL-C (R2=0.32). Conclusion: Lp-PLA2 activity was only associated with apo B adjusted for several confounding variables, suggesting that its clinical utility to identify individuals at risk for CVD does not surpass LDL-C and apo B in healthy adolescents. As plaque morphology may change with age, associations of Lp-PLA2 with CVD may likewise vary with age.